Sociopolitical consequences of COVID-19 in the Americas, Europe, and Asia: A multilevel, multicountry investigation of risk perceptions and support for antidemocratic practices - José J. Pizarro; Huseyin Cakal; Lander Méndez; Larraitz N. Zumeta; Marcela Gracia-Leiva; Nekane Basabe; Ginés Navarro-Carrillo; Ana-Maria Cazan; Saeed Keshavarzi; Wilson López-López; Illia Yahiiaiev; Carolina Alzugaray-Ponce; et al. (Wiley, 2024)
Although different social crises may eventually favorundemocratic and authoritarian forms of governance,at some point, such antidemocratic practices require thesupport of a signAlthough different social crises may eventually favorundemocratic and authoritarian forms of governance,at some point, such antidemocratic practices require thesupport of a significant part of the population to be im-plemented. The present research investigates how andwhether the COVID-19 pandemic might have favouredgreater support for antidemocratic governmental prac-tices, on the premise of regaining control and security.Using data from 17 countries (N = 4364) and national-levelindicators (i.e., real number of contagions and deaths, andsociopolitical indicators), we test how the risk of contagionand death from COVID-19, along with personal orienta-tions (i.e., social dominance orientation [SDO], right-wingauthoritarianism [RWA], and perceived anomie) motivateauthoritarian and antidemocratic practices. Results frommultilevel models indicate that risk perception and per-ceptions of political instability predict a wish for strongerleadership, agreement with martial law, and support for acontrolling government especially when SDO and RWAare high, while more egalitarian and less conservative peo-ple agree less with these authoritarian measures in spite ofthe levels of risk perception. We discuss the implicationsfor these findings for future research on similar but alsodissimilar external events (natural disasters, war, or terrorincidents) and the consequences for societies with higherauthoritarian tendencies.ificant part of the population to be im-plemented. The present research investigates how andwhether the COVID-19 pandemic might have favouredgreater support for antidemocratic governmental prac-tices, on the premise of regaining control and security.Using data from 17 countries (N = 4364) and national-levelindicators (i.e., real number of contagions and deaths, andsociopolitical indicators), we test how the risk of contagionand death from COVID-19, along with personal orienta-tions (i.e., social dominance orientation [SDO], right-wingauthoritarianism [RWA], and perceived anomie) motivateauthoritarian and antidemocratic practices. Results frommultilevel models indicate that risk perception and per-ceptions of political instability predict a wish for strongerleadership, agreement with martial law, and support for acontrolling government especially when SDO and RWAare high, while more egalitarian and less conservative peo-ple agree less with these authoritarian measures in spite ofthe levels of risk perception. We discuss the implicationsfor these findings for future research on similar but alsodissimilar external events (natural disasters, war, or terrorincidents) and the consequences for societies with higherauthoritarian tendencies.